Reshaping of the nominal inflection in early Northern West Germanic - Adamczyk, Elżbieta, 1976- (North-Western European language evolution. Supplement ;, 2018)
"The book is a comprehensive corpus study of analogical developments in the nominal morphology of four Northern West Germanic languages: Old English, Old Frisian, Old Saxon and Old Low Franconian. It examines the patterns of reorganisation of the nominal paradigms, focusing on the analogical interdeclensional shifts of nouns affiliated with historical minor classes. The wide scope and comparative nature of the study facilitate identifying the major patterns of inflectional restructuring, both language-specific and those of a more general character, demonstrating that the process was far from random. By framing the investigated phenomena quantitatively, the study affords insight into the dynamics of the changes, their scope in individual languages, the mechanisms underlying the restructuring process and the factors conditioning it. The book may be of interest to both historical linguists who may appreciate its descriptive aspects as well as morphologists concerned with the mechanisms of morphological processes, especially analogy"--